2011
DOI: 10.5402/2011/876502
|View full text |Cite
|
Sign up to set email alerts
|

Low-Protein Diet during Lactation and Maternal Metabolism in Rats

Abstract: Some metabolic alterations were evaluated in Wistar rats which received control or low-protein (17%; 6%) diets, from the pregnancy until the end of lactation: control non-lactating (CNL), lactating (CL), low-protein non-lactating (LPNL) and lactating (LPL) groups. Despite the increased food intake by LPL dams, both LP groups reduced protein intake and final body mass was lower in LPL. Higher serum glucose occurred in both LP groups. Lactation induced lower insulin and glucagon levels, but these were reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 40 publications
(50 reference statements)
5
30
0
Order By: Relevance
“…It has been explored whether the amount of dietary protein could affect the levels of circulating prolactin. Moretto et al clearly demonstrated that in fact when rats consumed a low protein diet, the concentration of serum prolactin was significantly reduced [22]. Our results also demonstrated that the dietary protein/carbohydrate ratio influences the serum prolactin concentration.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been explored whether the amount of dietary protein could affect the levels of circulating prolactin. Moretto et al clearly demonstrated that in fact when rats consumed a low protein diet, the concentration of serum prolactin was significantly reduced [22]. Our results also demonstrated that the dietary protein/carbohydrate ratio influences the serum prolactin concentration.…”
Section: Discussionsupporting
confidence: 86%
“…The lower the amount of protein, the lower the concentration of serum prolactin [22]. As a result there is a decrease in milk production that is reflected in the growth pattern of the pups.…”
Section: Introductionmentioning
confidence: 96%
“…Second, maternal protein restriction alters hepatic lipid content in male offspring rats [124] and promotes the hepatic accumulation of lipids, leading to a high incidence of fatty liver [125].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Low-protein diets reduce serum prolactin by 70%, evidenced by less suckling and milk production, which in turn does not promote leptin resistance, characteristic of this phase 27 . Shaw et al 25 stated that the third week of pregnancy is characterized by continuous hyperinsulinemia and insulin resistance.…”
Section: Discussionmentioning
confidence: 98%